-
Notifications
You must be signed in to change notification settings - Fork 19
/
basis_P1_2D.tex
208 lines (197 loc) · 5.45 KB
/
basis_P1_2D.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
\begin{flushright} {\tiny {\color{gray} basis\_P1\_2D.tex}} \end{flushright}
%~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
Here we do not start from a reference element but consider instead a generic triangle:
\input{tikz/tikz_P1}
This is the simplest 2D element, which is also called linear triangular element.
Velocities (or displacements) $(u^h,v^h)$ in the element are interpolated from nodal velocities
$(u_i,v_i)$ using basis functions $\bN_i$ as follows,
\[
\vec\upnu^h=
\left(
\begin{array}{c}
u^h(x,y) \\v^h(x,y)
\end{array}
\right)
=
\left(
\begin{array}{c}
\sum_{i=1}^3 \bN_i(x,y) u_i \\
\sum_{i=1}^3 \bN_i(x,y) v_i
\end{array}
\right)
=
\left(
\begin{array}{cccccc}
\bN_1(x,y) & 0 & \bN_2(x,y) & 0 & \bN_3(x,y) & 0\\
0 & \bN_1(x,y) & 0 & \bN_2(x,y) & 0 & \bN_3(x,y)\\
\end{array}
\right)
\cdot
\left(
\begin{array}{c}
u_1 \\ v_1 \\ u_2 \\ v_2 \\ u_3 \\ v_3
\end{array}
\right)
\]
or simply
For this element, we have three nodes at the vertices of the triangle, which are
numbered around the element in the counterclockwise direction.
Each node has two degrees of freedom (i.e. it can move in the $x$ and $y$ directions).
The velocities $u^h$ and $v^h$ are assumed to be linear functions within the element, that is,
\begin{eqnarray}
u^h(x,y)&=&b_1 +b_2x+b_3y \nn\\
v^h(x,y)&=&b_4 +b_5x+b_6y
\end{eqnarray}
where $b_i$ are constants to be determined and which depend on the triangle shape.
Note that the strain rate components are then given by
\begin{eqnarray}
\dot\varepsilon_{xx}(\vec\upnu)&=&b_2 \nn\\
\dot\varepsilon_{yy}(\vec\upnu)&=&b_6 \nn\\
\dot\varepsilon_{xy}(\vec\upnu)&=&(b_3+b_5)/2 \nn
\end{eqnarray}
and are constant throughout the element.
The velocities should satisfy the following six equations (when it is evaluated at a node we should
recover the nodal velocity):
\begin{eqnarray}
u_1 &=& u^h(x_1,y_1)= b_1 + b_2x_1+b_3y_1 \nn\\
u_2 &=& u^h(x_2,y_2)= b_1 + b_2x_2+b_3y_2 \nn\\
u_3 &=& u^h(x_3,y_3)= b_1 + b_2x_3+b_3y_3 \nn\\
v_1 &=& v^h(x_1,y_1)= b_4 + b_5x_1+b_6y_1 \nn\\
v_2 &=& v^h(x_2,y_2)= b_4 + b_5x_2+b_6y_2 \nn\\
v_3 &=& v^h(x_3,y_3)= b_4 + b_5x_3+b_6y_3 \nn
\end{eqnarray}
Let us focus on the three equations with the $u$ component of the velocity.
These can be re-written:
\[
\left(
\begin{array}{c}
u_1 \\ u_2 \\ u_3
\end{array}
\right)
=
\left(
\begin{array}{ccc}
1 & x_1 & y_1 \\
1 & x_2 & y_2 \\
1 & x_3 & y_3 \\
\end{array}
\right)
\cdot
\left(
\begin{array}{c}
b_1 \\ b_2 \\ b_3
\end{array}
\right)
\]
In order to obtain $b_1,b_2,b_3$ we need to solve this system, or simply to compute the
inverse of the $3\times 3$ ${\bm M}$ matrix, as explained in Appendix~\ref{sec:inv3x3}.
We define $D={\rm det}({\bm M})$ and we get
\[
\left(
\begin{array}{c}
b_1 \\ b_2 \\ b_3
\end{array}
\right)
=
\frac{1}{D}
\tilde{\bm M}
\cdot
\left(
\begin{array}{c}
u_1 \\ u_2 \\ u_3
\end{array}
\right)
%\qquad
%{\rm and}
%\qquad
%\left(
%\begin{array}{c}
%b_4 \\ b_5 \\ b_6
%\end{array}
%\right)
%=
%\frac{1}{D}
%\tilde{\bm M}
%\cdot
%\left(
%\begin{array}{c}
%v_1 \\ v_2 \\ v_3
%\end{array}
%\right)
\]
The matrix $\tilde{\bm M}$ is given by:
\[
\tilde{\bm M}
%=
%\left(
%\begin{array}{ccc}
% x_2y_3-x_3y_2 & -(y_3-y_2) & x_3-x_2 \\
%-(x_1y_3-x_3y_1) & y_3-y_1 & -(x_3-x_1) \\
% x_1y_2-x_2y_1 & -(y_2-y_1) & x_2-x_1
%\end{array}
%\right)
=
\left(
\begin{array}{ccc}
x_2y_3-x_3y_2 & x_3y_1-x_1y_3 & x_1y_2-x_2y_1 \\
y_2-y_3 & y_3-y_1 & y_1-y_2 \\
x_3-x_2 & x_1-x_3 & x_2-x_1
\end{array}
\right)
\]
so that
\begin{eqnarray}
b_1 &=& \frac1D [ (x_2y_3-x_3y_2)u_1 + (x_3y_1-x_1y_3)u_2 + (x_1y_2-x_2y_1)u_3 ] \nn\\
b_2 &=& \frac1D [ (y_2-y_3)u_1 + (y_3-y_1)u_2 + (y_1-y_2)u_3 ] \nn\\
b_3 &=& \frac1D [ (x_3-x_2)u_1 + (x_1-x_3)u_2 + (x_2-x_1)u_3 ]
\end{eqnarray}
We then have
\begin{eqnarray}
u^h(x,y)
&=& b_1 + b_2 x + b_3 y \nn\\
&=&\frac1D [(x_2y_3-x_3y_2)u_1 + (x_3y_1-x_1y_3)u_2 + (x_1y_2-x_2y_1)u_3 ] \nn\\
&+&\frac1D [(y_2-y_3)u_1 + (y_3-y_1)u_2 + (y_1-y_2)u_3]x \nn\\
&+&\frac1D [(x_3-x_2)u_1 + (x_1-x_3)u_2 + (x_2-x_1)u_3]y \nn\\
&=&\frac1D [(x_2y_3-x_3y_2) + (y_2-y_3)x + (x_3-x_2)y]u_1\nn\\
&+&\frac1D [(x_3y_1-x_1y_3) + (y_3-y_1) x + (x_1-x_3) y]u_2 \nn\\
&+&\frac1D [(x_1y_2-x_2y_1) + (y_1-y_2) x + (x_2-x_1) y]u_3\nn\\
&=& \bN_1(x,y) u_1 + \bN_2(x,y) u_2 + \bN_3(x,y) u_3
\end{eqnarray}
with the linear basis functions are given by:
\begin{eqnarray}
\bN_1(x,y) &=& \frac{1}{D}[(x_2y_3-x_3y_2) + (y_2-y_3)x + (x_3-x_2)y] \nn\\
\bN_2(x,y) &=& \frac{1}{D}[(x_3y_1-x_1y_3) + (y_3-y_1)x + (x_1-x_3)y] \nn\\
\bN_3(x,y) &=& \frac{1}{D}[(x_1y_2-x_2y_1) + (y_1-y_2)x + (x_2-x_1)y] \nn
\end{eqnarray}
We can then easily verify that for example
\begin{eqnarray}
\bN_2(x_1,y_1)&=& \frac{1}{D}[(x_3y_1-x_1y_3) + (y_3-y_1)x_1 + (x_1-x_3)y_1] = 0 \\
\bN_2(x_2,y_2)&=& \frac{1}{D}[(x_3y_1-x_1y_3) + (y_3-y_1)x_2 + (x_1-x_3)y_2] = 1 \\
\bN_2(x_3,y_3)&=& \frac{1}{D}[(x_3y_1-x_1y_3) + (y_3-y_1)x_3 + (x_1-x_3)y_3] = 0
\end{eqnarray}
Note that the area $A$ of the triangle is given by:
\[
A=\frac{1}{2}D = \frac{1}{2}
\left|
\begin{array}{ccc}
1 & x_1 & y_1 \\
1 & x_2 & y_2 \\
1 & x_3 & y_3
\end{array}
\right|
\]
\noindent If we now consider the reference element in the reduced coordinates space $(r,s)$:
\input{tikz/tikz_P1ref}
The basis polynomial is then
\[
f(r,s) = a + br + cs
\]
and the basis functions:
\begin{mdframed}[backgroundcolor=blue!5]
\begin{eqnarray}
\bN_0(r,s) &=& 1-r-s \\
\bN_1(r,s) &=& r \\
\bN_2(r,s) &=& s
\end{eqnarray}
\end{mdframed}
Once again we can verify that $\bN_i(x_j,y_j)=\delta_{ij}$ and $\sum\limits_i \bN_i(r,s)=1$.